Impact of electronic Word-of-Mouth, product quality, and brand image on purchasing decisions in the skincare industry - Putri Sepfiani; Muhammad Lathief Ilhamy Nst; Muhammad Ikhsan Harahap (Journal of Enterprise and Development (JED), 2023)
Purpose — This paper aims to investigate how electronic Word of Mouth (e-WOM), product quality, and brand image influence consumer purchasing decisions in the skincare industry.Method —  This study utilizes a quantitative research method involving 100 consumers of cosrx skincare products as respondents. The researchers adopted non-probability sampling techniques, specifically purposive sampling, to select participants for the study. Primary data was collected through questionnaires distributed on Twitter, where respondents provided direct responses using a Likert scale. To analyze the data and assess the positive and significant effects, the researchers employed Partial Least Squares Structural Equation Modeling (PLS-SEM) version 4.0.Result — The findings of the study indicate that both e-WOM and product quality have a positive and statistically significant influence on consumer purchasing decisions. Additionally, the research highlights the mediating role played by brand image, which serves as a connecting factor between e-WOM, product quality, and the ultimate purchasing decisions of consumers. This suggests that a favorable brand image enhances the impact of positive e-WOM and product quality on consumers' willingness to make a purchase.Contribution — This research adds to the existing body of knowledge by specifically focusing on the skincare industry and providing empirical evidence for the interplay between e-WOM, product quality, brand image, and their influence on consumer purchasing decisions, while also uncovering the mediating role of brand image.